Hubungan subjective well being dengan perilaku pencegahan komplikasi diabetes mellitus berbasis teori health belief model - Prianti, Eka Agustina; Susanti, Dwi Agung; Maftukhin, Ahmad; Patonah, Siti (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Diabetes Mellitus is a metabolic disorder characterized by elevated blood sugar levels. Patients with diabetes are required to change their lifestyle to prevent complications. This makes them vulnerable to depression and have low subjective well-being. The Health Belief Model (HBM) theory is used to predict health behaviors based on an individual's perception of a disease. Purpose: To analyze the relationship between subjective well-being and behaviors to prevent complications of diabetes mellitus based on the health belief model theory. Method: This quantitative research used a correlational analytic design using a cross-sectional approach and purposive sampling design, meeting the inclusion criteria for 74 respondents. The instrument used a questionnaire and was analyzed using the Spearman rank test with a significance level of α ≤ 0.05. Results: This study showed that 74 respondents, with the majority (67 respondents (90.5%) having high subjective well-being and 59 respondents having good complication prevention behaviors. The Spearman rank test results showed a relationship between subjective well-being and behaviors preventing complications of diabetes mellitus based on the health belief model theory with a p-value of 0.005 < α = 0.05. Conclusion: Subjective well-being shows a relationship with behaviors preventing complications of diabetes mellitus. The HBM theory clarifies that healthy behavior is determined by an individual's acceptance and perception of the disease.   Keywords: Behavior; Diabetes Mellitus; Subjective Well-Being.   Pendahuluan: Diabetes Mellitus adalah penyakit gangguan metabolik yang ditandai dengan meningkatknya kadar gula dalam tubuh. Pasien DM dituntut merubah pola hidupnya untuk mencegah komplikasi. Hal ini menyebabkan pasien DM rentan depresi dan memiliki subjective well being yang rendah. Teori Health Belief Model (HBM) digunakan untuk memprediksi perilaku kesehatan pada persepsi individu  terhadap  suatu  penyakit. Tujuan: Untuk menganalisis hubungan antara subjective well being dengan perilaku pencegahan komplikasi diabetes mellitus berbasis teori health belief model. Metode: Penelitian kuantitatif dengan desain analitik korelasi menggunakan pendekatan cross sectional dan rancangan purposive sampling yang memenuhi kriteria inklusi sebanyak 74 responden. Instrumen menggunakan kuesioner dan dianalisis menggunakan uji spearman rank dengan tingkat kemaknaan α ≤ 0.05. Hasil: Penelitian ini menunjukkan 74 responden yaitu sebagian besar 67 responden (90.5%) memiliki subjective well being tinggi dan 59 responden memiliki perilaku pencegahan komplikasi baik. Hasil uji spearman rank ada Hubungan subjective well being dengan Perilaku Pencegahan Komplikasi Diabetes Melitus berbasis teori health belief model dengan nilai p value =0.005 < α = 0.05. Simpulan: Subjective well being menunjukkan adanya hubungan dengan perilaku pencegahan komplikasi diabetes mellitus, teori HBM memperjelas perilaku sehat ditentukan oleh penerimaan dan persepsi individu tentang penyakit.                                                   Kata Kunci: Diabetes Mellitus; Perilaku; Subjective Well-Being.